Cancer survivors in the labor market: Evidence from recent US micro-panel data - Ahmad Reshad Osmani; Albert A. Okunade (Economic Modelling, 2019)
Rising cancer survival rates and retiring at older ages improve the probability of labor market presence for cancer survivors. Yet, insufficient evidence exists on the labor market effects of male- and female- specific cancers. Therefore, using a theoretical construct of labor supply and health capital, this study exploits a nationally representative dataset, the 2008-2015 Medical Expenditure Panel Survey (MEPS), for estimating the correlated random effects (CRE) and over-dispersion empirical models to capture the job market effects for cancer survivors. After addressing the potential endogeneity of cancer and controlling for the number of years after cancer diagnoses, the estimated CRE model detect substantial male-female differences in the labor market outcomes for the survivors. Male and female cancer types adversely affect short- and long- run employment prospects, and male-specific cancers increase weekly hours of work and decrease short- and long- run annual labor incomes. Moreover, gender-specific cancers increasingly limit long run family incomes and raise total health expenditures in the short- and intermediate- runs but not in the long- run. Additionally, while the cancers increase the likelihood of missing a work day for both genders in the short-run the effect is larger for females. Finally, the total annual cost of workplace absenteeism for the employed male- and female- cancer survivors range from 0.58bn to 3.1 bn.
Keywords: C10; J22; I1; J29; 330; cancer survivors; labor market; correlated random effects; over-dispersion model; MEPS